A novel CpG ODN compound adjuvant enhances immune response to spike subunit vaccines of porcine epidemic diarrhea virus - Wang, Yating; Liu, Shijia; Li, Boshuo; Sun, Xinyao; Pan, Qi; Zheng, Yuxin; Liu, Jia; Zhao, Yongqiang; Wang, Jingyu; Liu, Liming; Du, Enqi (Frontiers in Immunology, 2024)
CpG oligodeoxynucleotides (CpG ODNs) boost the humoral and cellular immune responses to antigens through interaction with Toll-like receptor 9 (TLR9). These CpG ODNs have been extensively utilized in human vaccines. In our study, we evaluated five B-type CpG ODNs that have stimulatory effects on pigs by measuring the proliferation of porcine peripheral blood mononuclear cells (PBMCs) and assessing interferon gamma (IFN-γ) secretion. Furthermore, this study examined the immunoenhancing effects of the MF59 and CpG ODNs compound adjuvant in mouse and piglet models of porcine epidemic diarrhea virus (PEDV) subunit vaccine administration. The in vitro screening revealed that the CpG ODN named CpG5 significantly stimulated the proliferation of porcine PBMCs and elevated IFN-γ secretion levels. In the mouse vaccination model, CpG5 compound adjuvant significantly bolstered the humoral and cellular immune responses to the PEDV subunit vaccines, leading to Th1 immune responses characterized by increased IFN-γ and IgG2a levels. In piglets, the neutralizing antibody titer was significantly enhanced with CpG5 compound adjuvant, alongside a considerable increase in CD8+ T lymphocytes proportion. The combination of MF59 adjuvant and CpG5 exhibits a synergistic effect, resulting in an earlier, more intense, and long-lasting immune response in subunit vaccines for PEDV. This combination holds significant promise as a robust candidate for the development of vaccine adjuvant.